2014
DOI: 10.1016/j.chemosphere.2013.09.120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficiency of an experimental biocover to reduce BTEX emissions from landfill biogas

Abstract: Landfill emissions include volatile organic compounds (VOCs) and, particularly, benzene, toluene, ethyl-benzene and xylene isomers (collectively called BTEX). The latter are the most common VOCs found in landfill biogas. BTEX affect air quality and may be harmful to human health. In conjunction with a study aiming to evaluate the efficiency of passive methane oxidizing biocovers, a complementary project was developed with the specific goal of evaluating the reduction in VOC emissions due to the installation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A flux chamber was built in a similar way to those used by Capanema et al (2013) and Lakhouit et al (2014); as shown in Figure 1a. It covers an area equal to 4.5 m² with a total internal volume equal to 0.9 m³.…”
Section: Flux Chamber Specificationsmentioning
confidence: 99%
“…A flux chamber was built in a similar way to those used by Capanema et al (2013) and Lakhouit et al (2014); as shown in Figure 1a. It covers an area equal to 4.5 m² with a total internal volume equal to 0.9 m³.…”
Section: Flux Chamber Specificationsmentioning
confidence: 99%
“…Biofiltration systems are emerging technological solutions for the removal of methane and odors from LFG [13,14] when flaring is no longer feasible, which include different types, such as: biofilters [15,16]; biocovers [13,17,18]; and biowindows [17,19]; Based on previous small-scale studies [3,20], pilot scales of biocovers have been carried out to study methane removal [18,21,22]. In addition, studies on odor reduction [14,23] and simultaneous reduction of odors and methane [3,24,25] were also performed.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial inks are made from chemical compounds, typically volatile organic compounds (VOCs). The negative impact of VOCs concerning human health is well-known and documented in the relevant literature (Lakhouit et al, 2016;Lakhouit et al, 2014). Furthermore, at room temperature, certain VOCs are highly transmissible as emissions, thus affecting not only the mask wearer but also those around the wearer.…”
Section: Introductionmentioning
confidence: 97%